Urgensi Dialog Lintas Agama dan Upaya Mencari Titik Temu Ajaran Agama-agama Dalam Khazanah Kitab Tafsir - Fadhila Sidiq Permana (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2026)
This article examines the urgency of interfaith dialogue in the treasury of tafsir books, focusing on the interpretation of QS. Ali Imran verse 64. Interfaith dialogue has become an important agenda to maintain harmonious relations among religious communities, especially in Indonesia. A crisis in communication and dialogue has led to mutual suspicion, resulting in friction and conflict. This study aims to reveal the theological basis of interfaith dialogue contained in the Holy Qur'an, so that it can be useful as a foundation for agendas or forums promoting harmony among religious communities. The analysis uses a literature review method, referring to several tafsir books and various journal articles. The results of this research present several urgencies of interfaith dialogue found in tafsir books, such as efforts to uphold justice, religious moderation, and to find common ground between the teachings of Islam and those of other religions.